PENINGKATAN BUDAYA KERJA DALAM KONTEKS REFORMASI ADMINISTRASI DI PEMERINTAHAN KOTA SEMARANG - Sundarso Sundarso (Departemen Administrasi Publik, Universitas Diponegoro, 2015)
This study focused on: Work Culture (culture sets) Apparatus. The problem ofthis study were: 1) How is work culture conditions (culture sets) Apparatus inSemarang government and 2) whether the efforts that have been made inchanging and improving work culture (culture sets) Apparatus Semarang CityGovernment. Being objective of this study were: 1) To identify work cultureconditions (culture sets) Semarang City Government Apparatus 2) To draw upproposals as efforts to change and improve work culture Apparatus (culture sets)Semarang City Government.Work Culture (culturset) Apparatus in PERMENPAN-RB number 39 in 2012can be interpreted as: Attitudes and behavior of individ and groups within anorganization that is believed to be true and become habitual in implementing thetasks and jobs. Target of Workplace Culture (culturset) Apparatus is abureaucracy with integrity and high performance. Apparatus of integrity can beinterpreted as a civilian state apparatus shown good character by consistenttrustworthy behavior.Work culture conditions imaginable in Semarang city government inreforming the bureaucracy are: 1) civil servants who are not innovative anddoes not have the spirit of change is still quite a lot; 2) Implementation ofMental Activity Less than Optimal; 3) The penalty is not a deterrent effectdiscipline; and 4) It is not the establishment of a Working Culture. To overcomethese problems the proposed efforts to change and improve work culture(culturset) Semarang city government officials are as follows: 1) Implementguidance toward the development of regional innovation appropriate and basedon the field of duty sector departments; 2) Improve the quality of the activitiesof Mental apparatus. Implementation of mental and spiritual guidance toincrease the motivation of civil servants held eight times per year; 3)Development of a culture system of labor regulation Mayor (Perwal) SemarangNo. 18 of 2008 on Guidelines for Cultural Development Working within theGovernment Apparatus Pemekot by reviewing existing regulations tailored to thedynamics of the changing times. 4) Develop materials / curriculum Mindsettingin Pre Employment and Training of all levels and types of education andtraining in Semarang City Government Training Agency.Of the efforts that have been made can be seen: Integrity PNS views ofmanagement and staff commitment and discipline of civil servants.Commitment. Semarang City Government Leaders and staff are committed tothe implementation of the reform is high. As for discipline are still many civil servants who violate the discipline, performance evaluation results Kemenpan -RB to 438 district / municipal government throughout Indonesia in 2012 wherethe results show that out of 35 districts / cities in Central Java performance isworth an average of C (not good), even Rod district worth D. Can disimpilkanreforming work culture does not yet support achievement of high performingbureaucracy. Suggestions are proposed in order to change and improve workculture Apparatus (culture sets) Semarang City Government is to improve thediscipline of civil servants and improve bureaucratic performanceKeywords : Improvement of apparatus work culture; bureaucratic reform andthe Government of Semarang